Oropharyngeal Candidosis in HIV-Infected Patients—An Update - Shankargouda Patil; Barnali Majumdar; Sachin C. Sarode; Gargi S. Sarode; Kamran H. Awan (Frontiers in Microbiology, 2018)
Oropharyngeal candidosis (OPC) is an opportunistic fungal infection that is commonly found in HIV-infected patients, even in the twenty-first century. Candida albicans is the main pathogen, but other Candida species have been isolated. OPC usually presents months or years before other severe opportunistic infections and may indicate the presence or progression of HIV disease. The concept of OPC as a biofilm infection has changed our understanding of its pathobiology. Various anti-fungal agents (both topical and systemic) are available to treat OPC. However, anti-fungal resistance as a result of the long-term use of anti-fungal agents and recurrent oropharyngeal infection in AIDS patients require alternative anti-fungal therapies. In addition, both identifying the causative Candida species and conducting anti-fungal vulnerability testing can improve a clinician's ability to prescribe effective anti-fungal agents. The present review focuses on the current findings and therapeutic challenges for HIV-infected patients with OPC.